2003
DOI: 10.1177/1099800402239622
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Life Satisfaction in Subgrouped Fibromyalgia Patients

Abstract: The present study describes pain- and stress-coping strategies and life satisfaction in subgroups of fibromyalgia patients. Thirty-two females with fibromyalgia syndrome (FMS) and 21 healthy pain-free women were studied. Those with FMS were classified as thermal (both heat and cold) pain sensitive or slightly cold pain sensitive based on pain thresholds determined using a Thermotest device. Global stress-coping styles, life satisfaction, and specific pain-coping strategies were measured. Patients classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
(11 reference statements)
2
11
0
Order By: Relevance
“…Of the 22 selected studies for Sweden, six [29, 31, 34, 35, 42, 48] were judged as low risk of bias with results representative of the target population For the remaining 16, we judged eight to have a medium risk of bias [27, 28, 32, 3840, 45, 47] and eight as high risk of bias [2, 30, 33, 36, 37, 41, 43, 44, 46]. (Study [33] gives additional patient information on the cohort in Study [2] so these were classed as one study.)…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 selected studies for Sweden, six [29, 31, 34, 35, 42, 48] were judged as low risk of bias with results representative of the target population For the remaining 16, we judged eight to have a medium risk of bias [27, 28, 32, 3840, 45, 47] and eight as high risk of bias [2, 30, 33, 36, 37, 41, 43, 44, 46]. (Study [33] gives additional patient information on the cohort in Study [2] so these were classed as one study.)…”
Section: Resultsmentioning
confidence: 99%
“…Several authors reported heat or cold hypersensitivity in persons with FM (Jacobsen et al. 1993, Rogers & Maurizio 2000, Raak et al. 2003, Arnold et al.…”
Section: Discussionmentioning
confidence: 99%
“…Headache is a very common disorder amongst working people and tension‐type headache is the most prevalent headache type, affecting both women and men at some time in their lives. Tension‐type headache is also one of the most costly ailments in modern society because of its very high prevalence (1–3). The International Headache Society, in an attempt to provide standardized criteria for diagnosis, has grouped tension and tension‐vascular headaches under the term tension‐type headache.…”
Section: Introductionmentioning
confidence: 99%